Islamic Legal Perspectives on Local Traditions during Ramadan: A Case Study of Kanagarian Kamang Baru - Wafa Hidayatullah, A; Rades Putra, Auzai; Khaldi, Refli; Hamdani, Ripi; Amin, Muhammad (El-kahfi | Jurnal Ekonomi Islam, 2025)
This study investigates the integration between local customs (adat) and Islamic law (Sharia) in the context of Ramadan traditions in Kanagarian Kamang Baru, West Sumatra. Employing a qualitative ethnographic approach combined with normative Islamic legal analysis, the research explores how rituals such as balimau (pre-Ramadan purification), mangaji pasia (Qur'anic memorization by the sea), and inter-jorong communal iftar serve not only as cultural expressions but also as vehicles for religious devotion and communal identity. Data were gathered through observation, in-depth interviews with religious and customary leaders, and document analysis of local religious texts and practices. The findings demonstrate that while certain elements—particularly in balimau—pose ethical concerns from the standpoint of Islamic law (e.g., gender mixing), the community reconciles these practices through local interpretations rooted in ʿurf (custom). The synthesis between adat and Sharia is framed within the objectives of Islamic law (maqāṣid al-sharīʿah), emphasizing the values of purification, education, and social harmony. This research confirms that local traditions can enrich Islamic practice without violating its core principles, as long as proper ethical boundaries are maintained. The study contributes to the growing discourse on Islam Nusantara and advocates for context-sensitive Islamic legal frameworks that appreciate cultural diversity while upholding normative Islamic values. This paper underscores the role of religious scholars and traditional leaders in facilitating a balanced interpretation that resonates with both religious orthodoxy and local cultural wisdom.